2021
DOI: 10.3390/nu13072179
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Adherence to Four A Priori Dietary Indexes and Cardiometabolic Risk Factors among Hyperlipidemic Patients

Abstract: Little is known about which currently available a priori dietary indexes provide best guidance for reducing cardiometabolic risk factors (CMRF) among hyperlipidemic patients. This study was designed to compare the associations between four a priori dietary indexes, including Diet Balance Index (DBI-16), Chinese Healthy Eating Index (CHEI), Mediterranean Diet Score (MDS) and Dietary Approaches to Stop Hypertension (DASH) and CMRF among hyperlipidemic patients. A total of 269 participants were enrolled into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…The diet quality was quantified using DBI, which was established based on the recommended daily food intake from the CDGs (2022) and CFP (Supplementary Table 2). The scoring method and evaluation index of DBI were established with reference to the DBI_16 [ 39 ], see Supplementary Tables 3, 4, and 5.…”
Section: Methodsmentioning
confidence: 99%
“…The diet quality was quantified using DBI, which was established based on the recommended daily food intake from the CDGs (2022) and CFP (Supplementary Table 2). The scoring method and evaluation index of DBI were established with reference to the DBI_16 [ 39 ], see Supplementary Tables 3, 4, and 5.…”
Section: Methodsmentioning
confidence: 99%
“…Similar beneficial associations with the DASH score were also observed in prospective studies [ 12 , 17 , 52 ]. On the other hand, some studies found no association [ 18 , 20 ] or reported that this association disappeared after further adjustment for confounders [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, inverse associations between HEI, AHEI, and DASH scores and some cardiometabolic risk factors have been documented in observational [ 12 ] and interventional studies [ 13 , 14 ]. However, these findings are mainly derived from high-income countries, and their association with BP presents controversial results [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…To capture adherence to dietary recommendations during the COVID-19 pandemic, diet quality was quantified using the Diet Balance Index for Pregnancy (DBI-P), established with reference to the DBI_16 (for Chinese adults) ( 24 ) constitutive indicators, scoring method, evaluation index, and criteria.…”
Section: Methodsmentioning
confidence: 99%